Orquídeas [compact disc] - Uchis, Kali, 1993- (Geffen, 2024)
Grammy Award winner Kali Uchis releases her fourth studio album. Marking Uchis's striking return to Spanish-language music, the project features a superstar lineup with Karol G, Peso Pluma, El Alfa, and JT. Inspired by the sensual allure of Colombia's national flower, the orchid, it traverses multiple Latin genres including reggaeton, dembow, bolero, and salsa, furthering Uchis's connection to her Colombian roots.